Suplementação da dieta de bezerros em pastagem consorciada de aveia (Avena strigosa Schreb) e azevém (Lolium multiflorum Lam) com ou sem adição de cultura de levedura - Prohmann, Paulo Emílio Fernandes (2006)
These trials were carried out to evaluate animal performance, plasma urea concentration, ruminal parameters and sampling methods to estimate the diet chemical composition of calves grazing oat (Avena strigosa Schreb) and ryegrass (Lolium multiflorum Lam) mixed pasture, supplemented or not, with or without yeast culture addition. In the first trial were used thirty-two calves with eight months old and 187 kg of initial average weight from two genetic groups (½ Red Angus ½ Nelore and Red Brangus), under continuous grazing with variable stocking rate. Calves were randomly distributed in one of the following treatments: mineral mixture (MIS); mineral mixture + yeast culture (YEA); mineral mixture and supplementation with 1.2% of BW (SUP); and mineral mixture + yeast culture and supplementation with 1.2% of BW (YSU). Supplement was formulated with 23% of CP and 75% of TDN. Yeast culture was fed to provided 10 grams/animal/d. Estimatives of forage mass, daily accumulation rate and forage quality were made. Blood samples were collected for determination of plasma urea nitrogen (PUN). Yeast culture addition did not change average daily gain (ADG) neither weight gain per area (GPA) of animals exclusively on pasture or supplemented. ADG (kg/d) and GPA (kg/ha) altered during pasture cycle and were higher for SUP and YSU (0.809 and 554; 0.818 and 547, respectively) than MIS and YEA (0.610 and 304; 0.599 and 309, respectively). Difference on PUN concentration among treatments was not observed (23,9 mg/dL on average), however it was observed periods effect. The best benefit/cost ratio was presented by MIS, which obtained return of R$ 1.42 for each invested real. In the second trial, ruminal parameters of animals in the same conditions as described in the first experiment, were evaluated. Four Holstein steers, fitted with ruminal canullas, with 16 months old and 310 kg of body weight on average, were used. The experimental design was a 4 x 4 Latin square, consisted of 14 days periods, with 13 days for adaptation and one for collection. Ruminal liquid sampling was done before provide supplement and 2, 4 and 6 hours after. Only animals from SUP presented pH below 6. Yeast culture addition maintained pH mean value of 6.11 in animals that received YSU, however decreased the mean value of animals from YEA in comparison to MIS. Both, yeast addition and supplementation did not modify ruminal ammonia concentrations, that maintained above 22.5 mg/dL. In the third experiment, different sampling methods to estimate the chemical composition of steers diet on oat and ryegrass mixed pasture, were evaluated. The methods were: clipping close by soil (CCS), hand-plucking (HPL) and rumen evacuation (REV). Results indicated that rumen evacuation is the method that best characterize the diet consumed by steers on oat and ryegrass mixed pasture. Clipping close by soil and hand-plucking underestimated protein and energy concentration, and superestimated the amount of cell wall in the diet.